Problematika Kurikulum Merdeka di Sekolah Dasar: Antara Idealisme dan Realitas Pembelajaran - Arisma Salwa Hilmana; Muhammad Aqua Mutharik (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
The Independent Curriculum aims to provide flexible, student-centered learning that is oriented toward strengthening character through the Pancasila Student Profile. However, a literature review indicates that its implementation in elementary schools still faces various obstacles. Teachers' understanding of differentiated learning, the P5 project, and authentic assessment is uneven, while limited infrastructure and the complexity of developing teaching materials also hamper its implementation. Furthermore, student readiness and a supportive learning environment also influence the curriculum's effectiveness. These findings emphasize the need to improve teacher competency, ensure equitable distribution of facilities, and collaborate among stakeholders for optimal implementation of the Independent Curriculum. Furthermore, the disparity in the quality of implementation across schools is also a major challenge, particularly in remote areas with limited facilities. Therefore, supportive policies and intensive mentoring for teachers are needed to ensure that this curriculum is effective and provides maximum benefits for students, optimizing character development and 21st-century skills. Overall, the success of the Independent Curriculum depends heavily on solid collaboration between all relevant parties, including teachers, schools, parents, and education policymakers.